A second autopsy revealed the silent killer: A case of fatal carbon monoxide poisoning from gas geyser - Vora, Dipak H; Dewangan, Tikendra; Prabhakaran, S; Shah, Kalpesh A; Patel , Dharmesh S; Khubchandani , H T (Journal of Indian Academy of Forensic Medicine, 2021)
Carbon Monoxide (CO) is one of the important causes of accidental death in bathroom that occurs frequently due to installation of gas  geyser. CO is emitted from a gas geyser due to defect or poor maintenance. Blockage of the exit or 'flue' pipe is a common fault,  sometimes from bad installation or because it becomes blocked by soot or by birds' nests. Here, we present the case of 30-year-old  female found dead in her bathroom, whose second autopsy unveils the actual cause of death. Liquefied petroleum gas (LPG) or piped  natural gas (PNG) are used frequently in gas geyser for heating water in developing countries such as India. CO produces anemic  anoxia as well as tissue hypoxia by competing with oxygen for binding sites on oxygen carrying heme proteins like hemoglobin,  myoglobin, cytochrome-c oxidase and cytochrome p-450. This case highlights the importance of the second autopsy and role of  forensic medicine expert in determining the cause and manner of death so as to guiding police in proper investigation and preventing  the harassment of innocent people.
Keywords: Second autopsy; Silent killer; Carbon monoxide; Gas geyser